Molecular Identification and Phylogenetic Tree Reconstruction of Marine Fish from the Essential Wetland Area of Banyuwangi, Indonesia - Sapto Andriyono, ,- (Egyptian Society for the Development of Fisheries and Human Health, 2020)
Pangpang Bay is necessary to get serious attention because it is one of the essential wetlands in Banyuwangi, Indonesia. This area able to generate income for traditional fishers and ecological supports the surrounding area because it is possible to be a spawning area and nursery ground for many estuary fish. The identification of fisheries resources is carried out using a molecular approach in the Cytochrome oxidase subunit I (COI) region that is commonly used in barcoding. Identification with this method is expected to minimize errors in determining the name of the species of species that exist in Pangpang Bay. Based on molecular identification information in the COI region, 37 marine fish species were distributed in 25 families, and 4 orders. The results of this study are the initials of molecular information on fisheries resources in the Pangpang Bay area.